The Relationship of Parenting Patterns with Toddlers Nutritional Status in Wailolong Village, East Nusa Tenggara - Molan, Veronika Nogo; Sinaga, Masrida; Riwu, Rut Rosina (Universitas Nusa Cendana, 2023)
Toddlers are one of the groups at risk for nutritional problems. The intake of foods rich in nutrients has a good impact on the growth and development of children. Many factors influence the emergence of nutritional issues, including maternal parenting. This study aims to analyze the relationship of parenting with toddlers' nutritional status in Wailolong Village